2018
DOI: 10.1007/s00029-018-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

Cluster realization of $$\mathcal {U}_q(\mathfrak {g})$$ U q ( g ) and factorizations of the univers

Ivan C. H. Ip

Abstract: For each simple Lie algebra g, we construct an algebra embedding of the quantum group Uq(g) into certain quantum torus algebra Dg via the positive representations of split real quantum group. The quivers corresponding to Dg is obtained from amalgamation of two basic quivers, where each of them is mutation equivalent to the cluster structure of the moduli space of framed G-local system on a disk with 3 marked points when G is of classical type. We derive a factorization of the universal R-matrix into quantum di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…We mainly follow the notation in [FG09] and [GHK13] for the A and X cluster varieties. However, we slightly modify the definitions following [Nak21, Section 6], so that the mutation formulas for the A and X variables match that used by the first author in [Ip18], [Ip20] and also the original definitions in [FZ02]. (See Remark 2.8.)…”
Section: Preliminaries On Cluster Algebras 21 Basic Definitions and P...mentioning
confidence: 99%
See 4 more Smart Citations
“…We mainly follow the notation in [FG09] and [GHK13] for the A and X cluster varieties. However, we slightly modify the definitions following [Nak21, Section 6], so that the mutation formulas for the A and X variables match that used by the first author in [Ip18], [Ip20] and also the original definitions in [FZ02]. (See Remark 2.8.)…”
Section: Preliminaries On Cluster Algebras 21 Basic Definitions and P...mentioning
confidence: 99%
“…In [Ip18], the first author constructed a quiver D(i 0 ) for any reduced word i 0 of w 0 , and showed that there is an embedding D q (g) into the quantum cluster algebra O q for this quiver. The image of F i are telescoping sums along certain F i -paths, and the image of the K ′ i generators are monomials along the F i -paths.…”
Section: Punctured Disk Realizationmentioning
confidence: 99%
See 3 more Smart Citations